(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2024)
Deşli Caira in northern Dobrogea (Romania) is one of the key localities for the definition of the GSSP of the base of the Anisian stage. Eugen Grădinaru studied the Hallstatt limestones-facies of the Agighiol Limestone in this section for over 30 years, amassing a huge collection of ammonoids, and he also involved several specialists in the study of specific fossil groups. These ammonoids, which are the historical group for Triassic marine chronostratigraphy, have never been described until now. We present here the results of our ongoing study of the Grădinaru collection, including a new bed-by-bed sampling of the section and description of some Aegean taxa. The ammonoids consisting of 959 mostly juvenile specimens are not reelaborated, but are often preserved as hollow phragmocones filled by sediment or by sediment and cement. The ammonoid record of the section is dominated by leiostracan ammonoids, as is usual for the Ammonitico Rosso facies of the Agighiol Limestone. The Olenekian/Anisian Ammonoid Faunal Turnover (O/A AFT), the most significant turnover in the history of Triassic Ammonoidea, occurs within a 1.1 m-thick interval. We provide descriptions of Aegean ammonoids, i.e., Stenopopanoceras, Paracrochordiceras, Aegeiceras, Leiophyllites, as well as of Gradinaruites aegeicus n. gen. n. sp, Robinsonites simionescui n. sp. and Acrochordiceras sp. The ammonoid range chart, integrated with magnetostratigraphy and conodont chronostratigraphy, provides a new calibration of the GMPTS, and emphasizes the nearly coincident position of the O/A AFT with the base of magnetochron MT3. We present the correlation of the Deşli Caira section with the Chios, Kçira and Wantou sections, based on ammonoids and integrated stratigraphy and an overview of ammonoid faunal comparison with the most important O/A successions. Deşli Caira provides the best record of the O/A AFT with rich Aegean ammonoid faunas, allowing for the best calibration of the magnetochrons MT1-MT3. Therefore, we propose the combination of the O/A AFT with the base of MT3 as a powerful solution for the definition of the GSSP of the Anisian.